Dampak Covid-19 Terhadap Ekonomi Usaha Pariwisata Di Kawasan Pantai Kuta, Kabupaten Badung - I Gusti Ayu Made Sari Widiantari; I Putu Anom (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
Kuta Beach is a most popular destination and many tourism business affect the economy this area. TheKuta Beach area is so empty of visitors due to the impact of covid-19. Therefore, researchers conducted ananalysis of the impact of covid-19 on the economy of the tourism business in Kuta Beach, Badung Regency.In this study using the concept of critical management, the nation a pandemic, tourism emergencyresponse, tourism business and tourism attraction the type of data used is qualitatif data. Soulced fromsecondary data. Data collection techniques used by conducting library research, observation and interview.The data analysis technique used is qualitatif data techniques.The results of this study indicate that the impect of the covid-19 pandemic the economy. Especially thetourism business economy. In condition like this, it is very necessary far attention and policies from thegovernment so that the tourism busisness can rise.Keywords: Kuta Beach, Pandemic Covid-19, Tourism Business, Economy